Geruchsbezeichnungen in der Übersetzung am Beispiel des Romans Das Parfum. Die Geschichte eines Mörders von Patrick Süskind - PACHNIOWSKA, JOLANTA (Wydawnictwo Naukowe UAM, 2012)
The aim of the following article is to present the results of the translation of smell lexemes used in the Novel Parfume: The Story of a Murderer by Patrick Süskind and their Polish equivalents in Pachnidło. Historia pewnego mordercy by Małgorzata Łukasiewicz. The article discusses semantic, lexical and syntactical problems, influence of the context on the translation and the results of the analysis.
Keywords: Translation criticism; Semantics; Morphology; Syntax; Context; Translation analysis